Elderly dendritic cells respond to LPS/IFN-γ and CD40L stimulation despite incomplete maturation - Gardner, J.; Cornwall, S.; Musk, A.; Alvarez, J.; Mamotte, Cyril; Jackaman, Connie; Nowak, A.; Nelson, Delia (Public Library of Science, 2018)
There is evidence that dendritic cells (DCs) undergo age-related changes that modulate their function with their key role being priming antigen-specific effector T cells. This occurs once DCs develop into antigen-presenting cells in response to stimuli/danger signals. However, the effects of aging on DC responses to bacterial lipopolysaccharide (LPS), the proinflammatory cytokine interferon (IFN)-γ and CD40 ligand (CD40L) have not yet been systematically evaluated. We examined responses of blood myeloid (m)DC1s, mDC2s, plasmacytoid (p)DCs, and monocyte-derived DCs (MoDCs) from young (21–40 years) and elderly (60–84 years) healthy human volunteers to LPS/IFN-γ or CD40L stimulation. All elderly DC subsets demonstrated comparable up-regulation of co-stimulatory molecules (CD40, CD80 and/or CD86), intracellular pro-inflammatory cytokine levels (IFN-γ, tumour necrosis factor (TNF)-α, IL-6 and/or IL-12), and/or secreted cytokine levels (IFN-α, IFN-γ, TNF-α, and IL-12) to their younger counterparts. Furthermore, elderly-derived LPS/IFN-γ or CD40L-activated MoDCs induced similar or increased levels of CD8 + and CD4 + T cell proliferation, and similar T cell functional phenotypes, to their younger counterparts. However, elderly LPS/IFN-γ-activated MoDCs were unreliable in their ability to up-regulate chemokine (IL-8 and monocyte chemoattractant protein (MCP)-1) and IL-6 secretion, implying an inability to dependably induce an inflammatory response. A key age-related difference was that, unlike young-derived MoDCs that completely lost their ability to process antigen, elderly-derived MoDCs maintained their antigen processing ability after LPS/IFN-γ maturation, measured using the DQ-ovalbumin assay; this response implies incomplete maturation that may enable elderly DCs to continuously present antigen. These differences may impact on the efficacy of anti-pathogen and anti-tumour immune responses in the elderly.